Telecontrolling the Environmental Quality of Chilli Katokkon Plants Using the Internet Of Things - AISYAH NOVFITRI; Septriandi Wirayoga; Miftakhul Huda (Journal of Informatics and Communication Technology (JICT), 2025)
This research presents the design and implementation of an Internet of Things (IoT)-based environmental control system for optimizing the growth of Cabai Katokkon, a local chili variety from Toraja. The system integrates ESP32, pH sensors, temperature and humidity sensors, mist-based irrigation, and smart lighting (red and blue LEDs) to maintain optimal environmental conditions inside a greenhouse. Real-time monitoring and control are achieved through a mobile application, allowing remote management of temperature, humidity, soil pH, and lighting intensity. Over a four-month observation period, the system maintained soil pH within 5.3–6.5, temperature between 22–30°C, and humidity levels of 70–77%, all within optimal ranges for Cabai Katokkon growth. Automated misting and lighting systems responded effectively to sensor data, ensuring consistent environmental conditions. Results indicate that plants grown under this system showed improved growth rates, with increased stem height and diameter compared to traditional methods. This demonstrates that controlled environmental parameters significantly support photosynthesis and accelerate plant development. The system also proved efficient in reducing manual labor and minimizing human error. Overall, this IoT-based solution offers a modern, scalable approach to precision agriculture, especially in areas with limited natural light and space.